(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
A clever home or structure is a modern house or construction with special organized wiring that enables residents to control or program a variety of automatic household electrical devices remotely with a single order. Traditional security systems keep intruders at bay, keeping homeowners and their valuables safe. On either hand, a smart house protection system offers a host of extra benefits. Home automation technology notifies homeowners of possible problems, allowing them to investigate. This article discusses smart houses and security, as well as a smart home security technology. Whether you give your command by voice, tv remote, or computer, the home will fulfill it. The most popular uses include light, home protection, house theater and entertainment, and temperature adjustment. Security has been a serious worry in smart home technologies.